Unjukkerja Standar ZigBee pada WPAN dengan Topologi Mesh - Eka Wahyudi; Risanuri Hidayat; Sujoko Sumaryono (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2012)
ZigBee standard can be used in wireless sensor networks (WSN) with a mesh topology. WSN which formed WPAN that uses ZigBee standard has the capability to thousands of WSN devices can be combined in a single WPAN. With that ability need to do testing WPAN performance parameters to get the number of WSN devices for the best performance in mesh topology. Using simulation program, the research measure throughput, traffic (sent, receive and drop), delay and hop number parameters. Testing about the influence of the number of WSN devices is done by running a simulation of the 20 kind WPAN where every WPAN has one WSN gateway and the number of WSN devices ranging from 5 and increasingly by 5 to reach the 100 WSN devices in a single WPAN. The results showed that WPAN performance with ZigBee standard in mesh topology has the best conditions when the maximum number WSN devices achieve 20 WSN devices.